The role of sharia economics in supporting the realization of sustainable development goals and islamic development - Ariawan, Ariawan; Loso Judijanto; M. Yusuf Bahtiar; Farida Akbarina; Muhammad Syafri (ProBisnis : Jurnal Manajemen, 2024)
Environmentally Friendly Sustainable Development or Sustainable Development Goals is a policy program scheme agreed upon by world leaders to reduce poverty, inequality and end the impact of global climate change. This article discusses how the Sustainable Development Goals go hand in hand with Islamic development. The research method used in this literature review is descriptive qualitative. The study results show that the Islamic concept is in line/sustainable with the SDGs goals. Islam also has a way to fight poverty with zakat, fasting, and a simple lifestyle, providing equal rights between women and men and emphasizing that there is no equal position between the two; and orders humans to manage the environment wisely and maintain natural balance. Mobilizing the Islamic masses to help in achieving the SDGs as a form of their devotion to Allah SWT is a challenge for the government, community organizations and academics in socializing the SDGs and Sustainable Science to society and to higher education, especially Islamic religious universities (PTKI).